Supine positioning after vitrectomy for rhegmatogenous retinal detachments with inferior retinal breaks - Abdelkader, Amr Mohammed Elsayed (Int J Retina Vitreous, 2020)
BACKGROUND: To evaluate the effectiveness of face up position (FUP) following pars plana vitrectomy (PPV) and silicone oil injection in cases of rhegmatogenous retinal detachment (RRD) with multiple peripheral and inferior breaks. METHOD: Thirty-two eyes of 32 patients with RRD due to multiple peripheral breaks were managed with PPV and silicone oil as endotamponade. Postoperatively, all patients were instructed to assume face up (supine) position for at least 10 days. Silicone oil was removed 3 to 6 months postoperatively in eyes with attached retina and the patients were followed up for 6 months. RESULTS: Thirty eyes (94%) got a successful attachment of the retina and remained attached after silicone oil removal. One case showed lower redetachment under silicone oil while the other case showed recurrent RRD after silicone oil removal. CONCLUSION: Although postoperative FUP is not a popular one, it is effective in the treatment of RRD with peripheral breaks whatever the number or the distribution of these breaks. This may in some way or another change the traditional trends of postoperative positioning after vitrectomy for RRD.